Чехословацьке військо на Полтавщині (червень 1917 р. – березень 1918 р.): територія базування та службово-бойова діяльність - Головко, Г.; Головко, І.; Руднєва, М. (Краєзнавство, 2019)
У статті на підставі документальних джерел, головним чином полкових хронік і спогадів легіонерів, розглядаються особливості формування 2-ої чехословацької дивізії, а також вивчається питання
участі окремого Чехословацького армійського корпусу в боротьбі за владу в Україні в 1918 році. Following the Czechoslovak soldiers' stellar performance at Zborov, the Russian Provisional Government
finally granted their émigré leaders on the Czechoslovak National Council permission to mobilize Czech and
Slovak volunteers from the POW camps. In June 1917 the formation of second Czechoslovak Division, consisting
of four regiments, was begun. At the end of September, the division became part of the newly formed Special
Czechoslovak Corps.
Since only the defeat of Austro-Hungary and Germany offered any hope of Czech national independence,
Czechoslovak volunteers were amongst the most motivated and steadfast of the Allied forces in Russia.
In November 1917, the Bolsheviks seized power throughout Russia and soon began a war against the UNR.
After negotiations in Brest-Litovsk, the Central Powers became allies of Ukraine. The chairman of the
Czechoslovak National Council, T. Masaryk, who had arrived in Russia, began planning for the Legion's departure
from Russia and transfer to France so the Czechoslovaks could continue to fight against the Central
Powers. Since most of Russia's main ports were blockaded, Masaryk decided that the Legion should travel from
Ukraine to the Pacific port of Vladivostok, where the men would embark on transport vessels that would carry
them to Western Europe.
In February 1918, Bolshevik authorities in Ukraine granted Masaryk and his troop permission to begin
the journey to Vladivostok. However, on 18 February, before the Czechoslovaks had left Ukraine, the German
Army launched Operation «Faustschlag» (fist strike) on the Eastern Front to force the Soviet government to
accept its terms for peace. From 5 to 13 March, the Czechoslovak legionaries successfully fought off attempts
to prevent their evacuation in the fights near Hrebinka and Bakhmach and was started a long way to the east.
After returning home the Legion played a central part in the foundation of the Czechoslovakian nation.
The article on the basis of documental sources, basically the regimental chronicles and the legionary’s
memories, analyzes specifics of 2-nd Czechoslovak Division formation and also is being considered about the
participation of the Special Czechoslovak Corps in power struggles in Ukraine in 1918.
The soldiers and officers of the division were received military skills and necessary knowledge in Poltava’s
region. Boryspil, Piryatin, Baryshivka, Berezan, Yahotyn and Hoholeve were a cradle for 5-th, 6-th, 7-th, 8-th
rifle regiments, assault battalion and artillery regiment. But about this page of history, almost nothing is known
to the inhabitants of the region.